On some alleged "problems" and alleged "solutions" in democratic firms. Issue 2 (23rd September 2020) - Ellerman, David
Abstract : Purpose: This paper will discuss two problems that have plagued the literature on the Ward-Domar-Vanek labor-managed firm (LMF) model, the perverse supply response problem and the horizon problem. The paper also discusses the solution to the horizon problem and the alleged "solution" of a membership market. Design/methodology/approach: This is a conceptual paper so it analyzes the two problems and shows how they can be resolved. It also shows how one alleged "solution" (membership market) is based on several conceptual mistakes about the structure of rights in a democratic firm. Findings: The perverse supply response is based on the assumption that the members of a democratic firm can expel for no cause some members when it would benefit the remaining members. It is shown that the same perverse behavior happens conceptually and historically in a conventional firm under the same assumptions. The horizon problem is resolved by the system of internal capital accounts (ICAs) that has been independently invented at least four times. Research limitations/implications: The idea of a democratic firm is quite often dismissed by conventional economists: "At first it seems like a good idea but unfortunately it is plagued by structural problems such as the perverse supply response and the horizon problem." Hence it is important to see that the first is not a problem under ordinary assumptions and that the second is a solved problem. Practical implications: The perverse supply response problem can be reproduced in a conventional firm under similar assumptions, and the horizon problem is real problem for social or common ownership firms but is solved in the Mondragon-type worker cooperatives by the system of ICAs. This has been known and published since the early 1980s, but conventional economists ignore the solution and still cite it as an inherent structure problem of a democratic firm. Originality/value: It has not been previously shown in the LMF literature that the perverse supply response can be reproduced in a conventional corporation under similar assumptions since the maximand for the conventional firm is not total market value but that value per current shareholder. The solution to the horizon problem using ICAs has long been "known" but never acknowledged in the conventional literature as if it was a necessary feature of workplace democracy. The idea of a membership market is analyzed and criticized.